The Impact of Green Accounting, Sustainability Management, and Corporate Social Responsibility on the Profitability of Manufacturing Firms During the 2022–2024 Period - Joice Ruri Dhelia; Willy Yuliandhari (Journal of Economics and Management Scienties, 2026)
This study aims to examine the impact of green accounting, sustainability-oriented managerial practices, and corporate social responsibility (CSR) on the profitability of manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This research adopts a quantitative approach employing descriptive and verificative methods. The study utilizes secondary data obtained from the annual reports and sustainability reports of manufacturing companies. This study employs purposive sampling, a technique in which samples are selected based on specific criteria to ensure relevance to research variables such as green accounting, sustainability practices, and CSR, thereby enhancing data validity, resulting in a final sample of 15 manufacturing firms. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS Statistics version 26. The findings reveal that green accounting has a positive and significant effect on profitability, as measured by Return on Assets (ROA). In contrast, sustainability-oriented managerial practices and corporate social responsibility do not have a significant effect on profitability. These results suggest that the implementation of green accounting contributes directly to improving financial performance, while the benefits of sustainability management practices and CSR tend to be long-term in nature and have not yet generated immediate impacts on profitability during the observation period.